Energy Efficiency and Technological Progress of Agricultural Sector in China: Regional and Temporal Characteristics - Dr. Yasmin Akhtar; Dr. Fatima Gulzar; Shazia Khalid; Muhammad Asif (Indus Journal of Social Sciences, 2025)
Optimizing agricultural energy usage to maximize output with little impact on the environment is a pressing global concern. Energy efficiency (EE), total factor energy productivity (TFEP), and the narrowing of regional inequalities in agriculture technology are all goals of several initiatives put forward by the Chinese government. Energy efficiency, total factor energy productivity fluctuations, and the regional technology gap ratio (TGR) were assessed in this study, which examined 30 provinces in mainland China and three distinct regions from 2000 to 2020 using DEA Super-SBM, Meta Frontier Analysis, and the Malmquist-Luenberger index. With an average EE of 0.8492, the data show that China’s agricultural industry has space for a 15.08% improvement in EE development. Among the provinces in China, Qinghai has the highest energy efficiency rate at 1.5828, followed by Shanghai at 1.3716 and Hainan at 1.358. The Eastern area has an outstanding EE rating of 1.0532. The TGR grade in Zhejiang is an example of a modern method of agricultural production that efficiently utilizes energy resources. Total Grain Ratio (TGR) values over 0.96 and close to 1 in all provinces except Zhejiang indicate that China’s agricultural production technology is advanced. These states include Liaoning, Jiangsu, Shanghai, Guangdong, Ningxia, and Hainan. As time goes on, the eastern part of China’s technology gap ratio (TGR) becomes closer to 1 than the central and western areas. This demonstrates that the provinces in the east are using modern agricultural practices, which increase productivity by making greater use of the resources at their disposal. An MLI score of 1.103 indicates a 10.3% improvement in energy productivity throughout China’s agricultural sector. Subsequent studies showed that technological change (TC) was primarily responsible for the enhancement, with a TC value of 1.080, which was more than the EC value of 1.028. When comparing the three agricultural zones, the eastern zone produces more energy overall. In terms of total factor energy productivity, the four leading areas in China’s agricultural sector are Zhejiang (1.23), Shanghai (1.197), Liaoning (1.184), and Hebei (1.147). There were statistically significant differences in TGR and EE between the three sites, according to the Kruskal-Wallis test.